2015
DOI: 10.4103/0975-962x.155880
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory efficiency after rehabilitation of acquired maxillary and mandibular defects

Abstract: The effect of oral cancer with its therapeutic intervention involves significant facial and functional disabilities. It is customary to rehabilitate these patients by surgical or prosthetic means. Studies have been done to assess mastication and other functions after rehabilitation. A review of these studies for assessing masticatory function has been done under separate sections for maxillary and mandibular defects. Different masticatory tests are mentioned. Further scope for research has been highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Although, the mean scores on evaluation of OHRQL using the H&N35 questionnaire revealed general improvement on all the parameters evaluated following dental rehabilitation, only the social aspects were statistically significant following comparative analysis [p = 0.01]. This is in agreement with previous re-ports which suggested that dental rehabilitation has more impact on patients' cosmetic appearance than other aspects of oral functions [2] [20]. Methods employed include the use of bite force measurement, the use of test foods such as carrots and peanuts, assessment of tongue and cheek function, the use of Visual Analogue Scale to assess oral function and standardized questionnaires to get patients' level of satisfaction.…”
Section: Discussionsupporting
confidence: 82%
“…Although, the mean scores on evaluation of OHRQL using the H&N35 questionnaire revealed general improvement on all the parameters evaluated following dental rehabilitation, only the social aspects were statistically significant following comparative analysis [p = 0.01]. This is in agreement with previous re-ports which suggested that dental rehabilitation has more impact on patients' cosmetic appearance than other aspects of oral functions [2] [20]. Methods employed include the use of bite force measurement, the use of test foods such as carrots and peanuts, assessment of tongue and cheek function, the use of Visual Analogue Scale to assess oral function and standardized questionnaires to get patients' level of satisfaction.…”
Section: Discussionsupporting
confidence: 82%
“…Fabrication of a maxillary obturator is relatively easy for dentate patients. However, in patients with an edentulous maxilla, retention and stability of the prosthesis are problematic and will cause dysfunctions of mastication and pronunciation [1] [2]. Implant-supported full fixed prostheses (ISFPs) for the rehabilitation of edentulous jaws using osseo-integrated implants have been getting popular among dental clinicians.…”
Section: Introductionmentioning
confidence: 99%